Specialist-Woman Interaction System for Female Empowerment in Cases of Discrimination and Gender Violence - Casara, Wenceslao Arrascue (2023)
Gender violence and discrimination against women in Peru persist as a pressing social issue, demanding prioritized attention. Despite ongoing efforts, the prevalence of gender violence remains stubbornly high. A significant challenge in addressing this problem lies in the delayed reporting by victims to authorities or support organizations. On average, victims in Peru take 8 years and 8 months to report their ordeal, influenced by factors like fear of the aggressor, lack of information about available resources, and distrust in the justice system. In response, an integrated system has been developed to facilitate communication and support for victims. Comprising a cloud web platform and a virtual assistant, this system provides a secure and anonymous space for victims to share their concerns. The virtual assistant, or chatbot, serves as an intermediary, aiding victims in expressing their concerns and delivering pertinent information. Validation tests revealed that over 90% of participating women approved the chatbot as an effective means of interaction for obtaining information and scheduling appointments with specialists. This positive reception indicates that the system effectively fulfills its purpose of offering an accessible and confidential communication channel. Moreover, collaborating specialists have acknowledged the benefits of the system, noting its facilitation of regular tasks and improvement in patient interaction. Communication through the chatbot enhances specialists' understanding of victims' needs, contributing to more effective support.